2013
DOI: 10.3389/fphys.2013.00065
|View full text |Cite
|
Sign up to set email alerts
|

Trawling bats exploit an echo-acoustic ground effect

Abstract: A water surface acts not only as an optic mirror but also as an acoustic mirror. Echolocation calls emitted by bats at low heights above water are reflected away from the bat, and hence the background clutter is reduced. Moreover, targets on the surface create an enhanced echo. Here, we formally quantified the effect of the surface and target height on both target detection and -discrimination in a combined laboratory and field approach with Myotis daubentonii. In a two-alternative, forced-choice paradigm, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…The bats were held in captivity for over 6 months before the start of this experiment, and they adapted well to the captive environment. They also participated in other experiments, in which they caught mealworms from the water surface (Zseb€ ok et al, 2013). The bat keeping facility was located away from the roads, and care was taken that bats did not experience any continuous loud noise in captivity.…”
Section: Animals and Housingmentioning
confidence: 99%
“…The bats were held in captivity for over 6 months before the start of this experiment, and they adapted well to the captive environment. They also participated in other experiments, in which they caught mealworms from the water surface (Zseb€ ok et al, 2013). The bat keeping facility was located away from the roads, and care was taken that bats did not experience any continuous loud noise in captivity.…”
Section: Animals and Housingmentioning
confidence: 99%
“…Siemers et al (2001Siemers et al ( , 2005 showed that prey above water will become more conspicuous and thereby more easily detected by the acoustic mirror effect. Zsebok et al (2013) demonstrated that not only echo-acoustic prey detection, but also discrimination is optimized by a spatiotemporal integration of direct and indirect reflections from a water surface, termed the echo-acoustic ground effect.…”
mentioning
confidence: 99%
“…, , Zsebok et al. ). This is one of the reasons why bats mostly capture surface‐feeder fish that frequently break the water surface, rendering them detectable to echolocating bats.…”
Section: Resultsmentioning
confidence: 99%